Electrochemical construction of hierarchically ordered CdSe-sensitized TiO2 nanotube arrays : towards versatile photoelectrochemical water splitting and photoredox applications - Xiao, Fang-Xing (2014)
Recent years have witnessed quite a number of worldwide efforts for fabricating CdSe/TiO2 nanotube arrays (CdSe/TNTAs) nanocomposites; however, the construction of a well-defined CdSe/TNTAs binary nanostructure for versatile photocatalytic and photoelectrochemical applications still poses a big challenge. In this work, a hierarchically ordered CdSe/nanoporous TiO2 nanotube arrays (CdSe/NP-TNTAs) hybrid nanostructure was fabricated through a facile electrochemical deposition strategy. The combined structural and morphological characterizations show that the CdSe ingredients, consisting of clusters of quantum dots, were uniformly assembled on the inner and outer surfaces of the NP-TNTAs framework. It was demonstrated that the CdSe/NP-TNTAs heterostructure could be utilized as an efficient photoanode for photoelectrochemical water splitting; moreover, it could be used as a multifunctional photocatalyst for photoredox applications, including the photocatalytic oxidation of organic dye pollutants and the selective reduction of aromatic nitro compounds under visible light irradiation. Furthermore, photoelectrochemical and photocatalytic mechanisms over the CdSe/NP-TNTAs heterostructure were elucidated. In addition, the predominant active species during the photocatalytic process were systematically explored and unequivocally determined. It is hoped that this work could promote further interest in the fabrication of various one dimensional NP-TNTAs-based composite materials and their applications to photoelectrochemical water splitting and photocatalytic selective redox applications.